Mechanical Fatigue Resistance of Polydiketopyrrolo‐Pyrrole‐Dithienylthieno[3, 2‐b]thiophene‐Based Flexible Field‐Effect Transistors. Issue 13 (23rd March 2022) - Kubik, Paweł; Waliszewski, Witold; Nosal, Andrzej; Tomczyk, Mariusz; Adamski, Adrian; Gazicki‐Lipman, Maciej; Blom, Paul W. M.; Marszalek, Tomasz; Pisula, Wojciech
Abstract: Mechanical durability is one of the main obstacles of flexible organic electronic devices. In this work, the fatigue behavior of flexible field‐effect transistors based on a diketopyrrolo‐pyrrole‐dithienylthieno[3, 2‐b]thiophene polymer is reported. An especially for that purpose designed bending setup allows to perform precise multiple deformation cycles of the transistor channel area while monitoring the device behavior. The transistors show high operational stability upon 100 bending cycles at a radius of 500 µm. Bending at smaller radius of 100 µm leaves the functionality of the parylene dielectric intact but induces serious mechanical fractures in the semiconducting film. Despite macroscopic defects, the transistors still reveal good reliability including high charge carrier mobility, due to presence of sufficient pathways for the charge carrier transport and to a low gate leakage. It is also observed that thinner polymer films are more sensitive to the deformation‐induced defects leading to a larger decrease in device performance, especially during the initial bending cycles. In thicker DPP‐DTT films, the crack propagation less affects the semiconductor/dielectric interface, at which the main charge carrier transport take place, resulting in a more stable device operation. Therefore, the work provides fundamental understanding of the fatigue behavior of flexible transistors based on semiconducting polymers. Abstract : The mechanical durability of flexible field‐effect transistors based on a diketopyrrolo‐pyrrole‐dithienylthieno[3, 2‐b]thiophene polymer is investigated by means of a specially designed bending setup. At large bending radius, the transistors show high operational stability upon 100 bending cycles. Bending at smaller radius induces macroscopic defects, whereby the transistors still reveal good reliability and high charge carrier mobility.